Comparison of Semi-Cylindrical Recession Trochleoplasty and Trochlear Block Recession for the Treatment of Canine Medial Patellar Luxation: A Pilot Study - Blackford-Winders, Callie L.; Daubert, Michael; Rendahl, Aaron K.; Conzemius, Michael G. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to describe an alternative method for trochleoplasty, semi-cylindrical recession trochleoplasty (SCRT), and compare it to trochlear block recession (TBR) in regard to recessed trochlear depth, patellar depth, patellar articular contact with the trochlea, recessed trochlear surface area, procedure time, complications and functional outcome.Study Design Ten dogs with bilateral grade II-III medial patellar luxations underwent bilateral simultaneous correction surgery including tibial tuberosity transposition, lateral imbrication and trochleoplasty with one stifle each undergoing TBR and SCRT. Patients received pre-and postoperative stifle computed tomography scans and pre- and 8-week postoperative pressure platform analysis and physical examinations. Recessed trochlear depth, patellar depth, trochlear surface area, patellar articular contact, procedure time, complications and functional outcomes as measured by gait analysis were compared between the two techniques.Results There was no significant difference in measured outcome variables between techniques at any time point. At the time of the 8-week reassessment, no patella had reluxated.Conclusion Short-term follow-up shows similar functional outcomes between both techniques regarding rate of reluxation and limb function. The SCRT was subjectively easier to perform than TBR, particularly in small patients. The SCRT is an acceptable method of trochleoplasty for the treatment of medial patellar luxation in dogs and further studies evaluating long-term outcomes are justified.
Keywords: patellar luxation; stifle; dog; recession trochleoplasty; computed tomography